2020
DOI: 10.1093/nar/gkaa048
|View full text |Cite
|
Sign up to set email alerts
|

The m6A reader YTHDF1 promotes ovarian cancer progression via augmenting EIF3C translation

Abstract: N 6-Methyladenosine (m6A) is the most abundant RNA modification in mammal mRNAs and increasing evidence suggests the key roles of m6A in human tumorigenesis. However, whether m6A, especially its ‘reader’ YTHDF1, targets a gene involving in protein translation and thus affects overall protein production in cancer cells is largely unexplored. Here, using multi-omics analysis for ovarian cancer, we identified a novel mechanism involving EIF3C, a subunit of the protein translation initiation factor EIF3, as the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
423
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 532 publications
(472 citation statements)
references
References 54 publications
13
423
2
Order By: Relevance
“…Loss and gain functional studies confirmed that the reader YTHDF1 mediates m 6 A-increased translation of Snail mRNA [31]. Another recent report identified a novel mechanism involving the translation initiation factor EIF3C, as the direct target of the reader YTHDF1 [34]. YTHDF1 augments the translation of EIF3C by binding to m 6 A modified EIF3C mRNA and concomitantly promotes the overall translational output.…”
Section: A In Human Cancermentioning
confidence: 78%
See 1 more Smart Citation
“…Loss and gain functional studies confirmed that the reader YTHDF1 mediates m 6 A-increased translation of Snail mRNA [31]. Another recent report identified a novel mechanism involving the translation initiation factor EIF3C, as the direct target of the reader YTHDF1 [34]. YTHDF1 augments the translation of EIF3C by binding to m 6 A modified EIF3C mRNA and concomitantly promotes the overall translational output.…”
Section: A In Human Cancermentioning
confidence: 78%
“…YTHDF1 augments the translation of EIF3C by binding to m 6 A modified EIF3C mRNA and concomitantly promotes the overall translational output. Global translation rates are generally enhanced in cancer cells and altered translational control is a fundamental response to oncogenic stimulation.m 6 A methylome analysis also identified that multiple translation initiation factors were modulated by m 6 A, indicating that m 6 A modification could directly regulate the expression of translation associated factors, thereby facilitating tumorigenesis and metastasis of ovarian cancer [34]. The expression of YTHDF1 was found to be induced by the oncogenic transcription factorc-MYC, and this axis c-MYC/YTHDF1 promotes colon cancer cell proliferation and induces the resistance against anticancer drugs [35].…”
Section: A In Human Cancermentioning
confidence: 98%
“…EIF3C is a subunit of EIF3 which is indispensable for protein synthesis. YTHDF1 was highly expressed in ovarian cancer and targeted at EIF3C to enhance its translation efficiency via an m 6 A-dependent manner; therefore, affecting the overall translational output and regulating tumor cells proliferation, migration, and invasion [62].…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Diminishing the abundance of PRR5, PRR5L, and mTOR [61] Ovarian cancer YTHDF1 EIF3C Targeting at EIF3C to enhance its translation efficiency [62] Cervical cancer YTHDF2 GAS5 Abrogating the GAS5 expression [63] Melanoma YTHDF2 PD-1 (PDCD1), CXCR4, SOX10…”
Section: Itga6mentioning
confidence: 99%
“…The occurrence of m6A modi cation is encoded by methyltransferase complex. It can add, remove and read m6A sites respectively through the writer, eraser and reader [12][13][14][15].New evidences showed that by controlling the expression of oncogenes or tumor suppressor genes, m6A modi cation could regulate the occurrence, differentiation and metastasis of tumors [14,16,17]. METTL3 (methyltransferase like 3) is one of N6 methyladenosylmethy transferases, which plays an important role in mRNA pre-splicing, 3 '-terminal processing and translation regulation [18][19][20][21].According to recent studies, METTL3 can also in uence the tumorigenesis and growth of tumor by regulating the m6A modi cation [21][22][23].This mechanism has been found in a variety of tumor tissues [24][25][26].…”
Section: Introductionmentioning
confidence: 99%